Towards Sustainable Development: The Interconnection of Green Corporate Govarnance and Green Finance in Cemara Asri’s SMEs: PENGARUH GREEN CORPORATE GOVARNANCE DAN KEUANGAN HIJAU TERHADAP KINERJA BERKELANJUTAN UMKM (Studi Kasus Pada UMKM di Cemara Asri, Medan) - Wita Syahdana; Deliyanti Simbolon (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to find out whether Green Corporate Govarnance and Green Finance have a significant effect on the Sustainability Performance of MSMEs in Cemara Asri, Medan. This study uses quantitative data methods and the data source is primary data. The sampling technique uses saturated samples, so that the entire population is used as a sample of 60 MSMEs. Data analysis and testing consisted of validity tests, reliability tests, descriptive statistics, classical assumption tests, multiple regression analysis, partial (t test) and simultaneous hypothesis testing (F test), and determination coefficient tests (R2). The results of the study show that Green Corporate Govarnance has an effect and is significant on Sustainable Performance with a calculated t value of 3.905 < ttable 2, 00172 and a significant value of 0.000 < 0.05. Green Finance has a significant effect on Sustainable Performance with a calculated t value of 2.664 < ttable 2, 00172 with a significant level of 0.010 < 0.05. Simultaneously, Green Corporate Govarnance and Green Finance have a significant effect on Sustainable Performance with an Fvalue of 111.121 > Ftable 3.16 with a significance of 0.000 < 0.05 with a regression coefficient value of 79.6%.